Aspirin in the primary and secondary prevention of vascular disease: collaborative meta-analysis of individual participant data from randomised trials. - Baigent, C; Blackwell, L; Collins, R; Emberson, J; Godwin, J; Peto, R; Buring, J; Hennekens, C; Kearney, P; Meade, T; Patrono, C; Roncaglioni, M; et al. (Elsevier, 2009)
BACKGROUND: Low-dose aspirin is of definite and substantial net benefit for many people who already have occlusive vascular disease. We have assessed the benefits and risks in primary prevention. METHODS: We undertook meta-analyses of serious vascular events (myocardial infarction, stroke, or vascular death) and major bleeds in six primary prevention trials (95,000 individuals at low average risk, 660,000 person-years, 3554 serious vascular events) and 16 secondary prevention trials (17,000 individuals at high average risk, 43,000 person-years, 3306 serious vascular events) that compared long-term aspirin versus control. We report intention-to-treat analyses of first events during the scheduled treatment period. FINDINGS: In the primary prevention trials, aspirin allocation yielded a 12% proportional reduction in serious vascular events (0.51% aspirin vs 0.57% control per year, p=0.0001), due mainly to a reduction of about a fifth in non-fatal myocardial infarction (0.18%vs 0.23% per year, p<0.0001). The net effect on stroke was not significant (0.20%vs 0.21% per year, p=0.4: haemorrhagic stroke 0.04%vs 0.03%, p=0.05; other stroke 0.16%vs 0.18% per year, p=0.08). Vascular mortality did not differ significantly (0.19%vs 0.19% per year, p=0.7). Aspirin allocation increased major gastrointestinal and extracranial bleeds (0.10%vs 0.07% per year, p<0.0001), and the main risk factors for coronary disease were also risk factors for bleeding. In the secondary prevention trials, aspirin allocation yielded a greater absolute reduction in serious vascular events (6.7%vs 8.2% per year, p<0.0001), with a non-significant increase in haemorrhagic stroke but reductions of about a fifth in total stroke (2.08%vs 2.54% per year, p=0.002) and in coronary events (4.3%vs 5.3% per year, p<0.0001). In both primary and secondary prevention trials, the proportional reductions in the aggregate of all serious vascular events seemed similar for men and women. INTERPRETATION: In primary prevention without previous disease, aspirin is of uncertain net value as the reduction in occlusive events needs to be weighed against any increase in major bleeds. Further trials are in progress. FUNDING: UK Medical Research Council, British Heart Foundation, Cancer Research UK, and the European Community Biomed Programme.